The effectiveness of cognitive therapy on quality of life in patients with type II diabetes - Narges Mousavian; Adis Kraskian Mujembari; Alireza Aghayousefi (International Archives of Health Sciences, 2018)
Context: Patients with diabetes face various physical and psychological problems such as depression, anxiety, disability, low mobility and obesity leading eventually to decrease quality of life. As a result, life quality is so important about diabetes and its treatment. Aims: The aim of this study was to determine the effectiveness of cognitive therapy on quality of life in patients with diabetes. Subjects and Methods: The research method was semi-experimental with pretest/posttest/follow-up and control group design. The population of the research were included all patients with type II diabetes who were referred to the Diabetes Clinic of Ganjavian Hospital. The sample volume included 40 subjects and an available sampling method was applied. Moreover, the substitution between control group and experimental group was randomly implemented. To collect the data, diabetes quality of life questionnaire was used. The intervention group has been received therapeutic sessions, and the control group was in waiting list. Data were collected through questionnaire of quality of life. Results: The results of the covariance analysis showed that cognitive therapy improved the quality of life in the experimental group in the posttest and follow-up stage (P < 0.05). Cognitive therapy training can be effective in improving the quality of life in patients with type II diabetes (P < 0.05). Conclusion: In order to findings, it can be concluded that the presentation of cognitive therapy beside other medical interventions is as a part of comprehensive treatment and care of diabetes.